1999
DOI: 10.2337/diabetes.48.3.635
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional analysis of novel human melanocortin-4 receptor variants.

Abstract: Inactivation of the melanocortin-4 receptor (MC4-R) by gene-targeting results in mice that develop maturity-onset obesity, hyperinsulinemia, and hyperglycemia. These phenotypes resemble common forms of human obesity, which are late-onset and frequently accompanied by NIDDM. It is not clear whether sequence variation of the MC4-R gene contributes to obesity in humans. Therefore, we examined the human MC4-R gene polymorphism in 190 individuals ascertained on obesity status. Three allelic variants were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
2
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 0 publications
12
127
2
7
Order By: Relevance
“…Three adults were heterozygous for the Val103Ile variant and one for the Thr112Met variant, two previously reported polymorphisms. 9,18 Neither the third known polymorphism, Ile251Leu, 19 nor MC4R analysis in Belgian obese children and adults S Beckers et al pathogenic mutations in MC4R were found in our cohort of morbidly obese adult patients. The cohort of 123 children and adolescents was also screened for MC4R mutations.…”
Section: Resultscontrasting
confidence: 53%
See 3 more Smart Citations
“…Three adults were heterozygous for the Val103Ile variant and one for the Thr112Met variant, two previously reported polymorphisms. 9,18 Neither the third known polymorphism, Ile251Leu, 19 nor MC4R analysis in Belgian obese children and adults S Beckers et al pathogenic mutations in MC4R were found in our cohort of morbidly obese adult patients. The cohort of 123 children and adolescents was also screened for MC4R mutations.…”
Section: Resultscontrasting
confidence: 53%
“…35 However, functional analysis of all three polymorphisms did not indicate a difference to wild type MC4R. 14,15,18,34 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As primeiras descrições foram publicadas em outubro de 1998 por dois grupos diferentes na mesma edição da revista Nature Genetics (53,54). A partir daí, várias mutações foram descritas, com freqüências variando de menos de 0,5% a 5,8% (55)(56)(57)(58)(59)(60)(61)(62). As disparidades na prevalência de mutações patogênicas no MC4R, resultam, em parte, das diferenças étnicas e dos critérios de…”
Section: Receptor Da Melanocortina 4 (Mc4r)unclassified